Dato’ Yutitam in the Civil Court System of Thailand - Mahamatayuding Samah; Raihanah Abdullah; Mohd Norhusairi Mat Hussin; Nahid Ferdousi (AHKAM : Jurnal Ilmu Syariah, 2023)
Dato’ Yutitam is a Muslim judge authorized to deal with cases related to Islam together with a civil judge in the First Instance Court in the four Islamic provinces in southern Thailand. This authority is based on the provisions of the Act on the Application of Islamic Law in Pattani, Yala, Narathiwat and Satun 1946. Without Dato’ Yutitam, family cases cannot be decided. However, the power given to him is very limited, and his decisions cannot be appealed. This study relies on the study of documents and interviews with judges and the President of the Yala Islamic Religious Council to analyze the extent of the role taken by Dato’ Yutitam in making decisions on cases under the civil justice system of Thailand. This study reveals that a Dato’ Yutitam has limited power compared to civil judges, but he has a very positive impact on the Muslim community in the four southern regions of Thailand.  Abstrak: Dato’ Yutitam adalah seorang hakim Muslim yang berwenang menangani kasus-kasus yang berkaitan dengan Islam bersama dengan seorang hakim sipil di Pengadilan Tingkat Pertama di empat provinsi Islam di Thailand Selatan. Kewenangan ini didasarkan pada ketentuan Undang-Undang Penerapan Hukum Islam di Pattani, Yala, Narathiwat dan Satun 1946. Tanpa Dato’ Yutitam, kasus keluarga tidak dapat diputuskan. Namun, kekuasaan yang diberikan kepadanya sangat terbatas, dan keputusannya tidak dapat diajukan banding. Studi ini mengandalkan studi dokumen dan wawancara dengan hakim dan Presiden Dewan Agama Islam Yala untuk menganalisis sejauh mana peran yang diambil oleh Dato Yutitam dalam membuat keputusan kasus di bawah sistem peradilan perdata Thailand. Kajian ini mengungkapkan bahwa seorang Dato’ Yutitam memiliki kekuasaan yang terbatas dibandingkan dengan hakim sipil, namun ia memiliki dampak yang sangat positif bagi umat Islam di empat wilayah Thailand Selatan.